XRD analyses of InxGa1-xN (0.20 x 0.80) ternary alloys - Yushamdan, Yusof; Muslim, A. Abid; Ng, Sha Shiong; Haslan, Abu Hassan; Zainuriah, Hassan (Universiti Malaysia Perlis, 2010)
International Conference on X-Rays and Related Techniques in Research and Industry (ICXRI 2010) jointly organized by Universiti Malaysia Perlis (UniMAP) and X-Ray Application Malaysia Society (XAPP), 9th - 10th June 2010 at Aseania Resort Langkawi, Malaysia.